Teaching for understanding in medical classrooms using multimedia design principles. Issue 4 (12th March 2013) - Issa, Nabil; Mayer, Richard E.; Schuller, Mary; Wang, Edward; Shapiro, Michael B.; DaRosa, Debra A.
<x xml:space="preserve">Abstract</x> Objectives In line with a recent report entitled Effective Use of Educational Technology in Medical Education from the Association of American Medical Colleges Institute for Improving Medical Education (AAMC‐IME), this study examined whether revising a medical lecture based on evidence‐based principles of multimedia design would lead to improved long‐term transfer and retention in Year 3 medical students. A previous study yielded positive effects on an immediate retention test, but did not investigate long‐term effects. Methods In a pre‐test/post‐test control design, a cohort of 37 Year 3 medical students at a private, midwestern medical school received a bullet point‐based PowerPoint™ lecture on shock developed by the instructor as part of their core curriculum (the traditional condition group). Another cohort of 43 similar medical students received a lecture covering identical content using slides redesigned according to Mayer's evidence‐based principles of multimedia design (the modified condition group). Results Findings showed that the modified condition group significantly outscored the traditional condition group on delayed tests of transfer given 1 week (d = 0.83) and 4 weeks (d = 1.17) after instruction, and on delayed tests of retention given 1 week (d = 0.83) and 4 weeks (d = 0.79) after instruction. The modified condition group also significantly outperformed the traditional condition group on immediate tests of retention (d = 1.49) and transfer (d = 0.76). Conclusions This study provides the first evidence that applying multimedia design principles to an actual medical lecture has significant effects on measures of learner understanding (i.e. long‐term transfer and long‐term retention). This work reinforces the need to apply the science of learning and instruction in medical education.